Importance of Agroforestry Fruit Trees in Indigenous Health Practices of Tribes - Pandey, Sadhna; Varma, Shashi Kanta (Indian Journal of Agroforestry, 2020)
The main objective of the study is to investigate about the indigenous health practices as followed by tribes (belonging to Kaimur Bhabhua district in Bihar state) in relation to locally available fruit tree species and also to determine their scientific validity. The results indicate that four fruit trees suitable for agro forestry namely Bael (Aegle marmelos), Mango (Mangifera indica), Aonla (Emblica officinalis) and Ber (Ziziphus mauritiana) were found to be effectively used by the respondents in form of various indigenous health practices for curing their different health related problems. Out of these, usefulness of Bael against diarrhoea and dysentery were found to be scientifically relevant. While the other indigenous health technologies of Mango, Aonla and Ber as reported by the respondents were not found to be scientifically proven. Hence, there is a need to strengthen the scientific component lacking in these technologies for revival and revitalization of these traditional remedies and also to document other location specific indigenous technological knowledge.